Obesity and inflammation: reduced cytokine expression due to resveratrol in a human in vitro model of inflamed adipose tissue - Zagotta, Ivana; Dimova, Elitsa Y.; Debatin, Klaus-Michael; Wabitsch, Martin; Kietzmann, Thomas; Fischer-Posovszky, Pamela (Frontiers in Pharmacology, 2015)
Obesity is associated with an inflammatory status and linked with a number of pathophysiological complications among them cardiovascular disease, type 2 diabetes mellitus, or the metabolic syndrome. Resveratrol was proposed to improve obesity-related inflammatory problems, but the effect of resveratrol on cytokine expression in obesity is not completely understood. In this study, we used an in vitro model of human adipose tissue inflammation to examine the effects of resveratrol on the production of the inflammatory cytokines IL-6, IL-8, and MCP-1. We found that resveratrol reduced IL-6, IL-8, and MCP-1 levels in a concentration-dependent manner in adipocytes under inflammatory conditions. Further experiments showed that the action of resveratrol was mainly due to its NFkB inhibitory potential. Thus, our data support the concept that resveratrol can alleviate obesity-induced up-regulation of inflammatory cytokines providing a new insight towards novel treatment options in obesity.